Shelves tableware kombinasi material kayu dan baja ringan di Ujang Woodworks - Muhamad ridwan Alfariz; Maharani Dian Permanasari (Jurnal Desain Produk Nasional, 2025)
This study aims to develop the design of shelves tableware through the combination of wood and light steel materials at Ujang Woodworks. The research employs a qualitative method with a Design Thinking approach. The findings indicate that Ujang Woodworks has achieved significant innovation over the past four decades by developing shelves tableware with a combination of wood and light steel materials. This approach not only expands the spectrum of furniture design but also opens up opportunities for sustainable and innovative product development for this craftsmanship business. Keywords: Rack Equipment, Wood Furniture, Hollow Steel